The EU as a Global Trendsetter in the Fight Against Climate Change: Is a Climate-Neutral Europe by 2050 Feasible? - Mazur-Kumrić, Nives; Zeko-Pivač, Ivan (Pécs journal of international and European law, 2020)
On 11 December 2019, the European Commission published the Communication on the European Green Deal, preparing the ground for a new growth policy based on the ambitious climate and environmental objective of achieving a climate-neutral Europe by 2050. To that end, the European Green Deal has proposed the establishment of the Just Transition Mechanism, a robust funding scheme aiming to complement actions closely intertwined with the transition towards a low-carbon and climate-resilient future. Although of European provenance, the new growth strategy builds closely on the principles of the Paris Agreement – a landmark international legal act to combat climate change in the context of sustainable development and efforts to eradicate poverty. This paper examines the legal specificities of the green and just transition in the EU through the prism of the European Green Deal. The emphasis is on the role of the Just Transition Fund (JTF), the principal pillar of the Just Transition Mechanism, established and implemented under Cohesion policy rules to help the European economy and society become environmentally sustainable and conscious. In particular, the focus is on the possibilities offered by the new instrument in financing the diversification of local economy and mitigating negative impacts on employment, both alone and in conjunction with other instruments, mechanisms and facilities of the forthcoming financial period 2021 – 2027. In order to illustrate the manifold challenges of reshaping Cohesion policy in the course of the green transition, the paper also summarises the critical elements of the EU green reform at the time of the unprecedented COVID-19 crisis.